The Efficiency Of Tapered Steel Section With Perforation Under Shear Buckling Behaviour - Lock, Pui Yee (Universiti Sains Malaysia, 2018)
For optimization in construction, conventional I-beam is widely replaced by tapered and perforated section. The ideas of tapering and perforating the web of the section comes from the reason of ununiform moment gradient throughout the beam for most cases. The cross-sectional shape of beam is varied linearly to the moment gradient to achieve target of higher efficiency with lower cost. The redistribution of the stress from the applied load is caused by the tapering and perforating on the web profile. Hence, a non-linear finite element analysis was conducted to investigate the shear deformation pattern and efficiency of the tapered steel section with perforation in this research. A total of 148models were simulated via LUSAS software with the variables parameters fixed as tapering ratio, perforation shape, perforation size and perforation layout. The tapered steel section with perforation has lower critical shear buckling load and efficiency compared to tapered section without perforation but obtains a higher critical shear buckling load and efficiency compared to uniform section without perforation. The smaller the opening size and tapering ratio contributes to a larger of shear buckling capacity and efficiency of the section. The perforation layout with different perforation arrangement and spacing affect the shear strength and efficiency of the tapered steel section with perforation. The highest efficiency model is selected as section with 0.4D diamond perforation in layout 3 under tapering ratio of 0.3. The critical shear buckling load and efficiency is reduced 14.39% and 13.91% respectively when perforations are added onto the tapered steel section. A total of 0.56% steel material can be saved for same structural construction by using tapered steel section with perforation compared with tapered steel section without perforation.